O papel da caspase-8 na malária cerebral experimental - Larissa Marina Nogueira Pereira (2021)
Malaria is a disease caused by Plasmodium spp. parasites which affects millions of people every year. Exacerbated immune response by the host triggers a large production of inflammatory cytokines such as IL-1β and TNFα, contributing to the symptoms of the disease. During mouse malaria, although there is caspase-11 activation, the non-canonical pathway of inflammasome does not seem to contribute to the pathogenesis of the disease, whereas caspase-1 plays an important role on IL-1β production. Caspase-8 is cleaved in splenic monocytes from infected mice and caspase-8 participates in IL-1β and TNFα production. Moreover, Ripk3/Casp8-/- mice are partially resistant to infection followed by LPS challenge and experimental cerebral malaria and Ripk3/Casp8/1/11-/- e Ripk3/Casp8/Gsdmd-/- mice highly resistant in both models. These results demonstrate a complementary, but independent, role of caspase-8 and inflammasomes in mediating malaria pathogenesis. Besides, P. vivax and P. falciparum infected patients display active GSDMD, caspase-4 and caspase-8 in monocytes. In conclusion, the present work suggests the importance of caspase-8 during malaria and its potential role as a possible therapeutical target.